Interfacial microstructure and strength of brazed copper/porous copper foam towards the effect of porous copper foam pore density and brazing holding time. Issue 6 (16th June 2021) - Mohd Zahri, N.A.; Sahira Shafee, N.E.; Yusof, F.; Nurmaya Musa, S.; Liana Sukiman, N.; Haseeb, A.S.M.A.; Miyashita, Y.; Ariga, T.
Abstract: The porous copper foam was sandwiched between two coppers plate and then brazed using copper‐tin (9.7 %)‐nickel (5.7 %)‐phosphorus (7 %) filler foil. Brazing process was conducted to joint copper/porous copper foam by evaluating the effect of porous copper foam pore densities [pore per inch (PPI)] and brazing holding times. The brazed joint interface of copper and porous copper foam was characterised using Field emission scanning electron microscopy and Energy‐dispersive x‐ray spectroscopy for the microstructure and elemental composition analysis, respectively. X‐ray diffraction analysis was carried out on the shear fractured surfaces of brazed copper and porous copper foam for phase determination. The results exhibited distinct phases of copper (Cu), copper phosphide (Cu3 P), nickel phosphide (Ni3 P), and copper compound with tin (6 : 5) (Cu6 Sn5 ). The filler layer was formed as an island‐shaped that consists of copper phosphide and nickel phosphide. Prolong brazing holding time causes a thinner filler layer in brazing seam. While the non‐uniform thickness of the filler layer was observed at different pore densities of porous copper foam. The shear strength of brazed copper/porous copper foam 15 PPI with a 10 min brazing holding time yield a maximum shear strength of 2.9 MPa. Abstract : The copper/porous copper foam was brazed using a copper (Cu)‐tin (Sn)‐nickel (Ni)‐phosphorus (P) filler foil. The effect of brazing holding time and porous copper foam pore density played a vital role in microstructure and brazed joint strength. The filler foil wettability determines the interfacial microstructure of brazed copper/porous copper foam. Brittle intermetallic compounds give an effect on the shear strength of copper/porous copper foam.